1988
DOI: 10.1159/000469122
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization of Human Heart and Skeletal Muscle CK Isoenzymes

Abstract: The purpose of this study was to investigate the kinetic properties of human creatine kinase (CK) isoenzymes partially purified from heart and skeletal muscle. Utilizing the backward CK-catalyzed reaction of creatine phosphate + ADP ^ creatine + ATP, K values for heart and skeletal muscle CK MM (3.7 mmol/1) were significantly (p < 0.05) greater than CK MB (2.1 mmol/1) which were significantly (p < 0.05) greater than mitochondrial CK (1.8 mmol/1) at variable creatine phosphate and fixed ADP concentrations. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The PCr-to-Cr ratio, which dictates the free ADP concentration, is reduced with Cr loading, and this should, in theory, stimulate mitochondrial respiration. ADP appears to be restricted to the outer mitochondrial membrane in cardiac and type I muscle fibers (32), and this restriction might explain the influence of Cr on the rate of respiration in these fibers (33). Differences in the regulation of respiration between type I and type II skeletal muscle fibers have been reported previously, and this appears to result from differences in mitochondrial function (13,43).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The PCr-to-Cr ratio, which dictates the free ADP concentration, is reduced with Cr loading, and this should, in theory, stimulate mitochondrial respiration. ADP appears to be restricted to the outer mitochondrial membrane in cardiac and type I muscle fibers (32), and this restriction might explain the influence of Cr on the rate of respiration in these fibers (33). Differences in the regulation of respiration between type I and type II skeletal muscle fibers have been reported previously, and this appears to result from differences in mitochondrial function (13,43).…”
Section: Discussionmentioning
confidence: 61%
“…It has been proposed that a Cr-PCr shuttle exists in which Cr is transported to the mitochondria and PCr is delivered to the sites at which energy is required (7). The activity of Cr kinase in the mitochondrial intermembrane space is coupled with the rate of aerobic respiration (32), and it has been suggested that the increased rate of oxidative phosphorylation after the addition of Cr to cultures of cardiomyocytes results from an increased sensitivity of respiration to ADP (33). The PCr-to-Cr ratio, which dictates the free ADP concentration, is reduced with Cr loading, and this should, in theory, stimulate mitochondrial respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Meyer and Foley (32) have also reported differences in the regulation of oxygen consumption in ST and FT fibers. Moreover, the Mit-CK of the human gastrocnemius muscle has been shown to qualitatively and kinetically resemble that of heart muscle (1,40). The M-CK activity is also higher in human trained vs. untrained muscle (1) and higher in ST compared with FT muscle (48).…”
Section: Discussionmentioning
confidence: 90%